Weight Loss Is Associated With Increased NAD+/SIRT1 Expression But Reduced PARP Activity in White Adipose Tissue - Rappou, Elisabeth; Jukarainen, Sakari; Rinnankoski-Tuikka, Rita; Kaye, Sanna; Heinonen, Sini; Hakkarainen, Antti; Lundbom, Jesper; Lundbom, Nina; Saunavaara, Virva; Rissanen, Aila; Virtanen, Kirsi A.; Pirinen, Eija; et al. (The journal of clinical endocrinology and metabolism, 2016)
Context:Sirtuins (SIRTs) and poly(ADP-ribose) polymerases (PARPs) are 2 important nicotinamide adenine dinucleotide (NAD)+-dependent enzyme families with opposing metabolic effects. Energy shortage increases NAD+ biosynthesis and SIRT activity but reduces PARP activity in animals. Effects of energy balance on these pathways in humans are unknown.Objective:We compared NAD+/SIRT pathway expressions and PARP activities in sc adipose tissue (SAT) between lean and obese subjects and investigated their change in the obese subjects during a 12-month weight loss.Design, Setting and Participants:SAT biopsies were obtained from 19 clinically healthy obese subjects (mean ± SE body mass index, 34.6 ± 2.7 kg/m2) during a weight-loss intervention (0, 5, and 12 mo) and from 19 lean reference subjects (body mass index, 22.7 ± 1.1 kg/m2) at baseline.Main Outcome Measures:SAT mRNA expressions of SIRTs 1–7 and the rate-limiting gene in NAD+ biosynthesis, nicotinamide phosphoribosyltransferase (NAMPT) were measured by Affymetrix, and total PARP activity by ELISA kit.Results: SIRT1, SIRT3, SIRT7, and NAMPT expressions were significantly lower, whereas total PARP activity was increased in obese compared with lean subjects. SIRT1 and NAMPT expressions increased in obese subjects between 0 and 5 months, after a mean weight loss of 11.7%. In subjects who continued to lose weight between 5 and 12 months, SIRT1 expression increased progressively, whereas in subjects with weight regain, SIRT1 reverted to baseline levels. PARP activity significantly decreased in all subjects upon weight loss.Conclusions:Calorie restriction is an attractive strategy to improve the NAD+/SIRT pathway and decrease PARPs in SAT in human obesity.